The “Silent” Global Burden of Congenital Cytomegalovirus - Manicklal, Sheetal (American Society for Microbiology, 2013)
Human cytomegalovirus (CMV) is a leading cause of congenital infections worldwide. In the developed world, following the virtual elimination of circulating rubella, it is the commonest nongenetic cause of childhood hearing loss and an important cause of neurodevelopmental delay. The seroprevalence of CMV in adults and the incidence of congenital CMV infection are highest in developing countries (1 to 5% of births) and are most likely driven by nonprimary maternal infections. However, reliable estimates of prevalence and outcome from developing countries are not available. This is largely due to the dogma that maternal preexisting seroimmunity virtually eliminates the risk for sequelae. However, recent data demonstrating similar rates of sequelae, especially hearing loss, following primary and nonprimary maternal infection have underscored the importance of congenital CMV infection in resource-poor settings. Although a significant proportion of congenital CMV infections are attributable to maternal primary infection in well-resourced settings, the absence of specific interventions for seronegative mothers and uncertainty about fetal prognosis have discouraged routine maternal antibody screening. Despite these challenges, encouraging results from prototype vaccines have been reported, and the first randomized phase III trials of prenatal interventions and prolonged postnatal antiviral therapy are under way. Successful implementation of strategies to prevent or reduce the burden of congenital CMV infection will require heightened global awareness among clinicians and the general population. In this review, we highlight the global epidemiology of congenital CMV and the implications of growing knowledge in areas of prevention, diagnosis, prognosis, and management for both low (50 to 70%)- and high (>70%)-seroprevalence settings.